Angiographic and Clinical Impact of Successful Manual Thrombus Aspiration in Diabetic Patients Undergoing Primary PCI - Mohamed Shehata (International Journal of Vascular Medicine)
Background. Diabetes mellitus is associated with worse angiographic and clinical outcomes after percutaneous coronary intervention (PCI). Aim. To investigate the impact of manual thrombus aspiration on in-stent restenosis (ISR) and clinical outcome in patients treated by bare-metal stent (BMS) implantation for ST-segment elevation myocardial infarction (STEMI). Methods. 100 diabetic patients were prospectively enrolled. They were randomly assigned to undergo either standard primary PCI (group A, 50 patients) or PCI with thrombus aspiration using Export catheter (group B, 50 patients). The primary endpoint was the rate of eight-month ISR. The secondary endpoint included follow-up for major adverse cardiac events (MACE). Results. Mean age of the study cohort was 59.86±8.3 years, with 64 (64%) being males. Baseline characteristics did not differ between both groups. Eight-month angiogram showed that group B patients had significantly less late lumen loss (0.17±0.35 versus 0.60±0.42 mm, P<0.001), with lower incidence of ISR (4% versus 16.6%, P<0.001). There was a trend towards lower rate of MACE in the same group of patients. Conclusion. In diabetic patients undergoing primary PCI, manual thrombus aspiration (compared with standard PCI) was associated with better ISR rate after BMS implantation.